The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1007/s11434-013-5852-9
|View full text |Cite
|
Sign up to set email alerts
|

Negatively and positively charged bacterial aerosol concentration and diversity in natural environments

Abstract: Bioaerosol charge information is of vital importance for their electrostatic collection. Here, electrostatic means and molecular tools were applied to studying bioaerosol charge dynamics. Positively or negatively charged bioaerosols were collected using an electrostatic sampler operated with a field strength of 1.1 kV cm −1 at a flow rate of 3 L min −1 for 40 min. Those with fewer or no charges bypassing the sampler were also collected using a filter at the downstream of the electrostatic sampler in one enviro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Indeed, although more investigations are requested, several recent publications [30,31] showed that electrostatic field would damage the culturability of collected bio-particles (bacteria, fungi and other cellular derivatives) due to the excessively charged stress. Furthermore, the particle collection by unipolar charge systems causes a significant difference compared with real results in monitoring a collection due to the intrinsic charge of bioparticles.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, although more investigations are requested, several recent publications [30,31] showed that electrostatic field would damage the culturability of collected bio-particles (bacteria, fungi and other cellular derivatives) due to the excessively charged stress. Furthermore, the particle collection by unipolar charge systems causes a significant difference compared with real results in monitoring a collection due to the intrinsic charge of bioparticles.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the particle collection by unipolar charge systems causes a significant difference compared with real results in monitoring a collection due to the intrinsic charge of bioparticles. It is up to the charge polarities of particles and generator, the error could be up to 50% as represented in [30].…”
Section: Introductionmentioning
confidence: 99%
“…Electric field extracts charged microbes from the flow. Microbes are naturally charged [38,39]; therefore, in an electric field, they are impelled towards the electrode of opposite polarity. Figure 1 depicts this process schematically.…”
Section: Resultsmentioning
confidence: 99%
“…Consistent with this, Yao and Mainelis (2006) reported that airborne microorganisms encountered in indoor and outdoor environments carried either net negative or net positive charges. Results obtained by Shen, Wei, and Yao (2013) also showed that the positively and negatively charged culturable bacterial aerosol concentration and diversity varied with sampling environment. After dispersal in a field environment, the microorganisms gradually return to their natural charge state, which depends on their cell structure (Lee et al, 2004).…”
Section: Introductionmentioning
confidence: 86%